Perencanaan Kurikulum - Batubara, Khairunnisa (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Curriculum planning involves a series of organizational methods that are focused on achieving optimal student understanding. Educators are usually responsible for ensuring that their curriculum planning meets the educational needs of students. Students receive new knowledge, attitudes and skills information that changes their behavior to better learning as evidence of implementing the established curriculum.